2020
DOI: 10.1371/journal.pone.0233853
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of Escherichia coli using bacteriophage-induced lysis and image analysis

Abstract: Rapid detection of bacterial pathogens is a critical unmet need for both food and environmental samples such as irrigation water. As a part of the Food safety Modernization Act (FSMA), The Produce Safety rule has established several requirements for testing for the presence of generic Escherichia coli in water, but the current method available for testing (EPA M1603) demands specified multiple colony verification and highly trained personnel to perform these tests. The purpose of the study was to assess a phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
1
16
0
1
Order By: Relevance
“…Moreover, using soluble substrates requires the release of enzyme from cells to the aqueous phase, which may not be efficient as alkaline phosphatase have high molecular weight of 94 kDa. In our prior research, we have observed a significant retention of cellular content including DNA and cell membrane after bacteriophage lysis of cells (Yang et al, 2020). Thus, an extended time of incubation may result in more efficient release of enzymes from residual cellular content after lysis as well as multiple repeat cycles of phage infection and the expression of exogenous enzyme can increase the effective enzyme concentration.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, using soluble substrates requires the release of enzyme from cells to the aqueous phase, which may not be efficient as alkaline phosphatase have high molecular weight of 94 kDa. In our prior research, we have observed a significant retention of cellular content including DNA and cell membrane after bacteriophage lysis of cells (Yang et al, 2020). Thus, an extended time of incubation may result in more efficient release of enzymes from residual cellular content after lysis as well as multiple repeat cycles of phage infection and the expression of exogenous enzyme can increase the effective enzyme concentration.…”
Section: Discussionmentioning
confidence: 97%
“…The fact that T7 bacteriophage genome is relatively simple has allowed multiple genetic modifications by inserting different reporter genes. A number of phage-based bacteria detection approaches have been discussed and improved for higher bacteria detection sensitivity [ 14 , 17 , 29 , 30 ]. To extend the applicability of this system, our study offers a straightforward and rapid strategy using engineered T7 phages to detect E. coli in ground beef.…”
Section: Discussionmentioning
confidence: 99%
“…in fluid from orthopedic artificial joints [53]. Other methods have visualized the change in redox reactions by Salmonella enterica Typhi and Paratyphi after phage infection [81], or measured the release of eDNA from phage infected E. coli [82]. Table 1 provides a detailed overview of phage amplification-based detection assays for bacterial pathogens.…”
Section: Phage Amplification-based Detectionmentioning
confidence: 99%